FORMATION OF HUMAN VALUES IN HIGH SCHOOL STUDENTS BY MEANS UKRAINIAN LITERATURE - L.O. Savchenko; L.V. Beshevets (Academy of Cognitive and Natural Sciences, 2007)
The article deals with some problems of value orientations in schoolboy life. The analysis of value orientations in pupl life in higher educational establishments of pedagogy is provided.